(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Andrew Marvell’s To His Coy Mistress is a masterful exploration of love, time, and mortality, enriched by its nuanced interplay of nature and politics. Through its three-part structure, the poem transitions from an idealized vision of timeless love to a stark confrontation with the inevitability of death, culminating in a call to seize the present. Marvell’s treatment of nature reflects both its beauty and its transience. Initially, nature is depicted as eternal and harmonious, framing a pastoral vision of love that transcends time. However, as the poem progresses, nature becomes a symbol of decay and mortality, underscoring the urgency of the speaker’s plea. The political dimensions of the poem emerge through its rhetoric and power dynamics. The speaker’s persuasive argument can be read as an allegory for political discourse, where flattery, logic, and coercion are tools used to assert control. This reflects the broader socio-political context of Marvell’s time, characterized by the instability of the English Civil War and Interregnum. The mistress, silent throughout, represents both the passive subject of persuasion and a potential symbol of resistance, inviting interpretations about agency within societal and political frameworks.